Prognostic and Immunological Value of Angiotensin-Converting Enzyme 2 in Pan-Cancer - Feng, Huan; Wei, Xian; Pang, Linhao; Wu, Yue; Hu, Bintao; Ruan, Yajun; Liu, Zhuo; Liu, Jihong; Wang, Tao (Frontiers in Molecular Biosciences, 2020)
Angiotensin-converting enzyme 2 (ACE2) plays a pivotal role in the renin-angiotensin system and has been found to be closely related to COVID-19. However, the role of ACE2 in cancers remains unclear. We explored the pan-cancer expression patterns and prognostic value of ACE2 across multiple databases, including Oncomine, PrognoScan, GEPIA, and Kaplan-Meier Plotter. Then, we investigated the correlations between ACE2 expression and immune infiltration in cancers. We found that tumor tissues had higher expression levels of ACE2 compared with normal tissue in kidney and liver, and lower expression levels in lung. High expression levels of ACE2 were beneficial to survival in ovarian serous cystadenocarcinoma, liver hepatocellular carcinoma, kidney renal papillary cell carcinoma, and kidney renal clear cell carcinoma, although this was not the case in lung squamous cell carcinoma. For those with a better prognosis, there were significant positive correlations between ACE2 expression and immune infiltrates, including B cells, CD8+ T cells, CD4+ T cells, neutrophils, macrophages, and dendritic cells. In conclusion, ACE2 could serve as a pan-cancer prognostic biomarker and is correlated with immune infiltrates.